Internet and Voting in the Web 2.0 Era: Evidence from a Local Broadband Policy - Samuele Poy; Simone Schüller (Center for Economic Studies and ifo Institute (CESifo), 2016)
This article analyzes the impact of a local broadband expansion policy on electoral turnout and party vote share. We exploit a unique policy intervention involving staged broadband infrastructure installation across rural municipalities in the Province of Trento (Italy), thus generating a source of exogenous (spatial and temporal) variation in the provision of advanced broadband technology (ADSL2+). Using a difference-in-differences strategy, we find positive effects of broadband availability on overall electoral turnout at national parliamentary elections. Party vote share analysis shows significant shifts across the ideological spectrum. These shifts, however, are likely transitory rather than persistent. Placebo estimations support a causal interpretation of our results. We provide further evidence that broadband availability is linked to actual adoption in that the broadband policy increased overall Internet and broadband take-up among private households.
Keywords: D72; L82; L86; 330; broadband internet; political participation; voting behavior; quasi-natural experiment